Saberes tradicionais quilombolas e a política nacional de assistência técnica e extensão rural: o caso do Arapapuzinho (Abaetetuba-PA) - GOMES, Rosenilda Botelho (Universidade Federal do Pará, 2019)
The quilombola people persevere in the struggle for the constitution of rights and, despite some achievements, are still in the process of accessing them fully. And, with the realization of ATER (Technical Assistance and Rural Extension) in the territory, which represents the scientific technical knowledge and the quilombolas with the traditional knowledge in the development of agriculture. And, with the effectiveness of ATER (Technical Assistance and Rural Extension) in the territory, which represents the scientific technical knowledge and the quilombolas with the traditional knowledge in the development of agriculture. Thus, this dissertation consists of analyzing whether ATER is contributing to the strengthening of family agriculture in the quilombola territory, with regard to productive organization, sustainable management and dialogue with the social and environmental knowledge of these traditional peoples in the community of Arapapuzinho, in Abaetetuba -PA. This research focused on this community where the quilombolas work in agriculture, using the knowledge passed from father to son. It brings to the discussion the role of the State and Social Movements in the National Policy of ATER (PNATER) for the quilombolas; the development of family farming activities through technical guidelines; the knowledge of quilombolas in plantations and crops in agriculture; and, finally, the mediation of the agents of development between the technical-scientific knowledge and the popular knowledge and the contributions of PNATER to the farmers. Through a Case Study, this research is supported by the following authors: Yin (2014); Gil (2008); Minayo (2013) and Triviños (1987), as well as authors who dialogue with the theoretical discussion about knowledge, among them: Diegues (2000, 2001); Cunha (2007) and others. However, we must emphasize the role of the State and those who debate on other issues, in this case ATER, like Schmitz (2003); public policies such as Pierre Muller; and Yves Surel (2000); and, among other themes, Freire (1983, 1987) and many other theorists who are subsidizing this text. Qualitative research, participant observation and semi-structured interviews were used for quilombola farmers, technicians and coordinator of COODERSUS (Cooperative for Work in Support of Sustainable Rural Development), who assisted the farmers, and representatives of the quilombola movement - ARQUIA (Association of Remnants of Quilombos of the Islands of Abaetetuba). The results highlight the strengthening of family agriculture, with the presence of ATER, and the cooperative presents an orientation innovation that seeks the economic, social and environmental interdependence that consolidates a sustainable development model. On the other hand, it shows that local development and productive increase are in the practices of technical knowledge, however, does not detract from traditional knowledge. We also have the resistance of the quilombolas to the technical orientation regarding the agroecological transition, even recognizing the importance of the ATER, these farmers continued to develop the activity of the agriculture and the management of the açaí according to their knowledge. The presence of conflicts and power relations was perceptible in the actions of ATER in the territory.